Mosaic APP Gene Recombination in Alzheimer's Disease—What's Next?. (May 2019) - Lee, Ming-Hsiang; Chun, Jerold
A first example of somatic gene recombination (SGR) within the human brain was recently reported, involving the well-known Alzheimer's disease (AD)-related gene amyloid precursor protein ( APP ). SGR was characterized by the creation of APP genomic complementary DNA (gencDNA) sequences that were identified in prefrontal cortical neurons from both normal and sporadic Alzheimer's disease (SAD) brains. Notably, SGR in SAD appeared to become dysregulated, producing many more numbers and forms of APP gencDNAs, including 11 single-nucleotide variations (SNVs) that are considered pathogenic APP mutations when they occur in families, yet are present mosaically among SAD neurons. APP gene transcription, reverse transcriptase (RT) activity, and DNA strand-breaks were shown to be three key factors required for APP gencDNA production. Many mechanistic details remain to be determined, particularly how APP gencDNAs are involved in AD initiation and progression. The possibility of reducing disease-related SGR through the use of RT inhibitors that are already FDA-approved for HIV and Hepatitis B treatment represents both a testable hypothesis for AD clinical trials and a genuine therapeutic option, where none currently exists, for AD patients.